The Direct/Indirect Association of ADHD/ODD Symptoms with Self-esteem, Self-perception, and Depression in Early Adolescents - Kita, Yosuke; Inoue, Yuki (Frontiers in Psychiatry, 2017)
The present study aimed to reveal the influences of attention-deficit hyperactivity disorder (ADHD) and oppositional defiant disorder (ODD) symptoms on self-esteem and self-perception during early adolescence, and to clarify the spillover effect of self-esteem on depressive symptoms. ADHD symptoms in 564 early adolescents were evaluated via teacher-rating scales. Self-esteem and depressive symptoms were assessed via self-reported scales. We analyzed the relationships among these symptoms using structural equation modeling. Severe inattentive symptoms decreased self-esteem and hyperactive–impulsive symptoms affected self-perception for non-academic domains. Although these ADHD symptoms did not directly affect depressive symptoms, low self-esteem led to severe depression. ODD symptoms had a direct impact on depression without the mediating effects of self-esteem. These results indicated that inattentive symptoms had a negative impact on self-esteem and an indirect negative effect on depressive symptoms in adolescents, even if ADHD symptoms were subthreshold. Severe ODD symptoms can be directly associated with depressive symptoms during early adolescence.